Perancangan Interior Museum Purbakala Di Situs Purbakala Patiayam, Kudus - Prajogo, Jessica Nathania (Intra, 2017)
As a cultural heritage, Patiyam Archaeological Site is an interesting place to travel back to prehistoric times. Many things that can be learned on this site, as examples about life in the past and about the mystery evolution of living beings, which is very interesting to be revealed. The purpose of designing the interior of archaeological museums in Patiayam ancient Site, Kudus, is as a place for education to the community and invites the community to participate in the preservation and restoration of cultural heritage. The design of this museum includes lobby area, gallery, souvenir shop, audio visual room and cafÃ©. The museum is designed using a linear circulation flow, in the order to let the visitor follow and pass through all the facilities within the museum.